2018
DOI: 10.21273/hortsci12987-18
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation of Buttonwood Tree (Conocarpus erectus) through Axillary Shoot Proliferation

Abstract: A method for micropropagation of Conocarpus erectus through axillary shoot proliferation is presented. Shoot tips were excised from adult donor tree and cultured for 4 weeks on Murashige and Skoog’s (MS) medium supplemented with 3 mg·L−1 gibberellic acid (GA3) to induce sprouting of shoots and formation of axillary shoots. Conocarpus erectus shoots were cultured for 6 weeks on MS medium supplemented with dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Our results indicate that lowering the salt strength in the medium to half resulted in 100% rooting of D. ombet, regardless of the concentration of IBA or NAA used. These results confirm previous findings on in vitro rooting of woody plant species such as Cassia angustifolia (Agrawal and Sardar 2007), Conocarpus erectus (Dewir et al, 2018), and Syzygium cordatum (Dewir et al, 2011), wherein the rooting was dependent on medium strength and the type and concentration of auxins. Regenerated plantlets of D. ombet were acclimatized to ex vitro conditions ( Fig.…”
Section: Treatmentssupporting
confidence: 91%
See 1 more Smart Citation
“…Our results indicate that lowering the salt strength in the medium to half resulted in 100% rooting of D. ombet, regardless of the concentration of IBA or NAA used. These results confirm previous findings on in vitro rooting of woody plant species such as Cassia angustifolia (Agrawal and Sardar 2007), Conocarpus erectus (Dewir et al, 2018), and Syzygium cordatum (Dewir et al, 2011), wherein the rooting was dependent on medium strength and the type and concentration of auxins. Regenerated plantlets of D. ombet were acclimatized to ex vitro conditions ( Fig.…”
Section: Treatmentssupporting
confidence: 91%
“…Successful shoot proliferation using BAP in combination with auxin has been reported in other Dracaena species, including D. deremensis (Singh et al, 2001), D. fragrans 'Massangeana' (Aziz et al, 1996), and D. marginata 'Tricolour' (El-Sawy et al, 2000). The synergistic increase in shoot proliferation as a result of the BAP and auxin combination has been reported in woody plant species, including, Arbutus unedo (2 mg · L -1 BAP and 0.5 mg · L -1 NAA; El-Mahrouk et al, 2010), Conocarpus erectus (2 mg · L -1 BAP and 0.5 mg · L -1 IBA; Dewir et al, 2018), and Lessertia frutescens (0.5 mg · L -1 BAP and 0.1 mg · L -1 NAA; Shaik et al, 2010).…”
Section: Resultsmentioning
confidence: 90%
“…No bacterial infection in other PVP-pretreated explants was observed because PVP was capable of reducing phenol leakage, and hence it supported preservation of high levels of phenolic compounds in explants to keep pathogens back from growing. In mango, significant reduction in infection extent was observed on explants treated with PVP (Krishna et al, 2008). In present study, it was found that applying PVP 0.5% to callogenesis culture medium of S. junceum L. prevented explants from browning.…”
Section: Discussionmentioning
confidence: 48%
“…However, they are able to induce necrotic explant and cell death in high concentration, and so cause browning of explants (Mahmoud and Al-Ani, 2016). In order to reduce browning degree, a number of approaches have been suggested (Krishna et al, 2008;Momeni et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Tissue browning occurs because of the accumulation and subsequent oxidation of phenolic compounds in the tissue and culture medium (Krishna et al, 2008;Uchendu et al, 2011). Oxidative browning causes slow growth and eventually leads to cell/tissue or plant death (Krishna et al, 2008;Dewir et al, 2018a) and has been reported to hinder the establishment of cultures of G. glabra (Shah and Dalal, 1980). Several other plant species such as Arbutus unedo (El-Mahrouk et al, 2010) and Conocarpus erectus (Dewir et al, 2018a) were also affected by oxidative browning.…”
Section: Resultsmentioning
confidence: 99%